KETIMPANGAN GENDER DI BALI: ANALISIS BUDAYA PATRIARKI, PERAN ADAT DAN AGAMA, SERTA RELEVANSINYA DI DUNIA MODERN - Galuh Anissa Sekar Ayu; Putra Ardiansyah; Royhan Ahmad Danarlie (Jurnal Harkat : Media Komunikasi Gender, 2022)
Abstract. This research is motivated by the patriarchal culture that is strongly embedded in the Balinese cultural system. The patriarchal culture that penetrates into the life of the Balinese people is predicted to be the biggest cause of gender inequality in various areas of people's lives. Gender inequality in the province of Bali can be found in the social, economic, cultural, political, and demographic fields. The main objective of this research is to provide answers to the formulation of the problem " How is the patrilineal system in Bali, the geographical location influencing patriarchal culture, and the roles of customs and religion contribute to gender inequality in the realms of family and society, and its relevance in the present day? The formulation of the problem will be answered using the concepts of liberal feminism, gender equality, and patriarchal culture with qualitative research methods. We argue that the patrilineal system is the biggest cause of imperial patriarchal culture and gender inequality in Bali. The research results indicate that the patrilineal system is closely related to the customs and norms of Balinese society. Moreover, the geographical location also contributes to the establishment of a patriarchal dominance in Bali. However, some Balinese communities perceive that the culture causing this gender imbalance is no longer relevant. Abstrak. Penelitian ini dilatarbelakangi oleh budaya patriarki yang melekat kuat dalam sistem kebudayaan masyarakat Bali. Budaya patriarki yang menelisik masuk ke dalam kehidupan masyarakat Bali digadang-gadang menjadi penyebab terbesar ketimpangan gender dalam berbagai bidang kehidupan masyarakatnya. Ketimpangan gender di Provinsi Bali banyak ditemui pada bidang sosial, ekonomi, budaya, politik, hingga kependudukan. Tujuan utama dari penelitian ini adalah untuk memberi jawaban atas rumusan masalah “Bagaimana kentalnya sistem patrilineal di Bali, lokasi geografis yang mempengaruhi budaya patriarki, dan peran adat serta agama menyebabkan ketimpangan gender pada ranah keluarga dan sosial serta relevansinya saat ini?" Rumusan masalah tersebut akan dijawab menggunakan konsep feminisme liberal, kesetaraan gender, dan budaya patriarki dengan metode penelitian kualitatif. peneliti berargumen sistem patrilineal menjadi penyebab terbesar kekaisaran budaya patriarki dan ketimpangan gender di Bali. Hasil penelitian menunjukkan sistem patrilineal berkaitan erat dengan adat dan norma masyarakat Bali. Pun letak geografis turut menentukan kekisaran patriarki di Bali. Beberapa masyarakat Bali menilai budaya yang menyebabkan ketimpangan gender ini dinilai sudah tidak relevan.